Possible Strategies for the Implementation of who Program on the Elimination of Hepatitis C in Ukraine by 2030 - Zaytsev, I.; Potii, V.; Kiriienko, V. (Journal of Education, Health and Sport, 2018)
Introduction. The article describes the model of natural history of hepatitis C virus the use of which makes it possible to assess the dynamics of the infected population from 2015 to 2030 in natural history and under the influence of the strategies of antiviral therapy, namely, the changes in the number of infected populations, the progression of the diseases, patients’ proportion with different stages of fibrosis and also the mortality which is associated with final stages of liver disease. In addition, there are estimated data on the number of the patients that are subject to annual diagnosing for treatment in accordance with specific therapy strategies which is necessary to achieve the results provided by the WHO program for the elimination of hepatitis C virus in Ukraine by 2030.Material and method. The study included 897 patients with chronic hepatitis C virus in whom the activity and stage of the disease were determined by liver biopsy or non-invasive tests (FibroTest, FibroTest / ActiTest, FibroMax). All the patients were divided by sex and age into the age groups with a 5-year interval: from 0 to 4 years, 5-9, 10-14, 15-19, 20-24, 25-29, 30-34, 35-39 , 40-44, 45-49, 50-54, 55-59, 60-64, 65-69, 70-74, 75 and more years.Results. According to the model of natural history of hepatitis C virus the number of the infected population in Ukraine should be reduced by 30% by 2030 of which 80% of the patients will die from decompensated LC and HCC. To reduce the mortality from final stages of liver disease 42.2% of the infected population should be treated according to selected therapy strategies. In this connection from 2016 to 2030 it is necessary to identify 65% and 77% of the patients with fibrosis stages F0-F4 for Strategies No. 1 and 2 respectively.Conclusion. To reduce the mortality from decompensated cirrhosis and hepatocellular carcinoma it’s necessary to treat 42.2% of the infected population according to selected treatment strategies. To treat the required number of the patients according to Strategies No. 1 and 2 it is necessary to identify 65% and 77% of the patients from the estimated number of infected populations respectively.Keywords: hepatitis C virus, natural history of hepatitis C virus, elimination of hepatitis C virus, mathematical modeling, fibrosis stage, therapy strategies, population prediction.